Analyses of Meta-Cognition of Middle School Students Based on Gender Differences in Solving Flat-Rectangular Space Problems - Ikrar, Ikrar; Aswad, Muhammad Hajarul; Ihsan, Muhammad (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2024)
Students with well-developed metacognition tend to excel in problem-solving. This study examines the metacognitive skills of junior high school (MTs) students in solving three-dimensional geometric problems, focusing on gender differences. The analysis involves three stages of metacognition: planning, monitoring, and evaluation. Using a qualitative descriptive approach, the study selected three male and three female students from 35 ninth-grade students. Data were gathered through mathematics learning outcome documents, metacognitive essay tests, and interview guidelines. The results reveal that male students face challenges across all three metacognitive stages when solving geometric problems, whereas female students encounter difficulties primarily at the evaluation stage. These findings highlight the need for targeted interventions to strengthen metacognitive skills, particularly in problem-solving contexts, while addressing gender-specific challenges.